CURRICULUM IMPLEMENTATION AND FACTORS INFLUENCING ACADEMIC ACHIEVEMENT IN CHEMISTRY: A NARRATIVE REVIEW OF COLLEGES OF EDUCATION IN NIGERIA - SHITTU, MUHIB LUQMAN; OLORUNDARE, ADEKUNLE SOLOMAN (Sokoto Educational Review, 2025)
This paper discusses curriculum implementation and the factors influencing students’ academic achievement in Chemistry within Colleges of Education. Curriculum implementation involves translating planned courses into syllabi and lessons delivered by teachers. Effective implementation is crucial for bridging the gap between intended and achieved learning outcomes. However, many well-designed curricula encounter problems during implementation. Teachers, who play a central role in this process, directly impact the quality of education. In Nigeria, teacher involvement in curriculum planning is often limited, raising concerns about effective implementation. Administrative staff also play a significant role. Monitoring curriculum implementation involves observation, feedback, interviews, student assessments, and reports. Several factors hinder effective implementation, including inadequate funding, insufficient facilities, economic factors, and inadequate planning. Researchers have also identified factors affecting students’ academic performance, such as communication, learning facilities, proper guidance, and family stress. Teacher-related variables, including age, gender, qualifications, and experience, also influence students’ achievement in Chemistry. While teacher qualification and experience can positively impact student outcomes, research findings vary. Teacher experience can also affect students’ study habits, with more experienced teachers often being more effective. In summary, this paper highlights the importance of effective curriculum implementation and how various factors, including teacher quality and student-related variables, can influence students’ academic achievement in Chemistry in Colleges of Education. DOI: https://doie.org/10.0302/SER.2025626646